O idiomatismo nas composições para quarteto de violões de Paulo Bellinati - Almeida, Joel Souza de (2020)
The Brazilian Paulo Bellinati (1950) is a classical guitarist, a guitar player, a musical producer and a composer with international recognition for his beautiful career as a solo concert performer and a chamber musician, especially with the Pau Brasil group. His compositions, played all around the world, encompass works for solo guitar, duo, trio and quartet, besides other formations. His music communicates a wide musical experience with characteristics that transcend classical and popular concepts, mixing theories and techniques with popular Brazilian sounds and rhythms. In some moments this happens with light dashes of the Jazz attributes. This research analyzes five works for guitar quartets by this composer, identifying and highlighting procedures and techniques that, in theory, serve as a reference for the elaboration of new arrangements and compositions for guitar quartet formation. The results were obtained through idiomatic and descriptive analyzes, seeking to recognize stylistic and genre information, instrumental techniques and compositional resources including the use of rhythmic and melodic patterns, harmonic sequencing, melodic developments, voicings, counterpoints, polyphonies and other techniques deployed by the arranger/composer.